Analisis Gen Patogenik iroN Escherichia coli Penyebab Kolibasilosis pada Ayam Kampung - Gunawan, Tania Ria; Mahardika, I Gusti Ngurah Kade; Besung, I Nengah Kerta; Suarjana, I Gusti Ketut (Jurnal Veteriner, 2020)
Avian colibacillosis is an infectious disease caused by avian pathogenic Escherichia coli (APEC). APEC ability to cause disease depends on many pathogenic factors, one of them is iroN pathogenic gene. This study purposed to find out iroN gene sequence in APEC in Bali. Two APEC isolates from free range chicken in Tabanan dan Badung has been used. The isolates have been been purified and were available at Laboratory of Veterinary Bacteriology, Faculty of Veterinary Medicine, Udayana University. Chelex 10%was used for DNA isolation. DNA amplification using published DNA primer has been conducted with polymerase chain reaction (PCR) method. The PCR product was sequenced at First Base Laboratories, Malaysia using Sanger’s Dideoxy Nucleotide Termination method. The iroN gene of both isolates can be analyzed and have 659 bp in length. Both were 100% homologous. Phylogenic test using 52 DNA sequence of  iroN gene from Escherichia coli and other bacteria in the world was conducted in MEGA 5.2. All data have 24 polymorphic sites of nucleotide acid and eight polymorphic sites of amino acid. The iroN gene of Bali isolates was in the same group as iroN gene from Australia (MF174860) and Hong Kong (MF474175). This gene can be used as pathogenic marker of APEC in Indonesia.